Continuous and intermittent exercise responses in individuals with chronic obstructive pulmonary disease. Issue 12 (24th November 2004) - Sabapathy, S; Kingsley, R A; Schneider, D A; Adams, L; Morris, N R
Abstract : Background: While the acute physiological responses to continuous exercise have been well documented in individuals with chronic obstructive pulmonary disease (COPD), no previous study has examined the response to intermittent exercise in these patients. Methods: We examined the physiological responses of 10 individuals with moderate COPD (forced expiratory volume in 1 second 52 (15)% predicted) who performed both an intermittent (1 min exercise and rest intervals) and a continuous cycle ergometer test on separate days. Both intermittent and continuous exercise tests were performed at the same power output, calculated as 70% of the peak power attained during an incremental exercise test. Results: Intermittent exercise was associated with significantly lower values for oxygen uptake, carbon dioxide output, expired ventilation, heart rate, plasma lactate concentration, and ratings of breathlessness than continuous exercise. Subjects were able to complete a significantly greater total amount of work during intermittent exercise (71 (32) kJ) than during continuous exercise (31 (24) kJ). The degree of dynamic lung hyperinflation (change in end expiratory lung volume) was significantly lower during intermittent exercise (0.23 (0.07) l) than in continuous exercise (0.52 (0.13) l). Conclusions: The greater amount of work performed and lower measured physiological responses achieved with intermittent exercise may allow for greater peripheral training adaptations in individuals with more limited lung function. The results suggest that intermittent exercise may be superior to continuous exercise as a mode of training for patients with COPD.